Pengaruh Ukuran Dewan Komisaris, Komite Audit, Kepemilikan Manajerial, Leverage, dan Ukuran Perusahaan terhadap Kinerja Keuangan - Sifa, Mufatih Ariska Sifananda; Ani Kusbandiyah; Iwan Fakhruddin; Dwi Winarni (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to examine the effect of the size of the board of commissioners, audit committee, managerial ownership, leverage, and company size on financial performance. The object of this research is the consumer cyclicals company in the 2019-2022 period. Good corporate governance mechanism is proxied by the size of the board of commissioners, audit committee, managerial ownership, leverage measured by Debt Asset Ratio (DAR), and company size measured by total assets, as well as financial performance measured by Current Ratio (CR). This type of research is quantitative research. The samples used in this study were obtained using purposive sampling methods based on predetermined criteria, namely from companies in the consumer cylicals sector. With a population of 33 companies that went public, the sample number was 132 financial statement observations. The method used in this study is multiple linear regression analysis using the SPSS program. Based on the results of the hypothesis t test, the size of the board of commissioners and the size of the company do not affect financial performance, the audit committee and leverage have a negative effect on financial performance, and managerial ownership has a positive effect on financial performance